310 CLINICAL COURSE AND CHARACTERISTICS OF ADVANCED HEART FAILURE ASSOCIATED WITH ARRHYTHMOGENIC CARDIOMYOPATHY. (15th December 2022) - Tini, Giacomo; Graziosi, Maddalena; Musumeci, Beatrice; Targetti, Mattia; Parisi, Vanda; Russo, Domitilla; Argirò, Alessia; Ditaranto, Raffaello; Basile, Ludovica; Imperatrice, Andrea; Zampieri, Mattia; Sclafani, Matteo; et al.
Abstract: Background: The prevalence and course of heart failure (HF) in arrhythmogenic cardiomyopathy (ACM) is unresolved, and previous studies have mostly focused on the right-dominant variant of the disease, less prone to HF. Conversely, ACM variants with left ventricular (LV) involvement are now increasingly recognized, often initially 'mis-diagnosed' as dilated cardiomyopathy. Aim of this study was therefore to describe the prevalence and clinical course of advance HF in the full clinical spectrum of ACM. Methods: We retrospectively reviewed records of all ACM patients diagnosed before 2021 from 3 Italian Cardiomyopathy Referral Centres (Azienda Ospedaliero Universitaria Careggi; Policlinico Sant'Orsola; Azienda Ospedaliero Universitaria Sant'Andrea). LV involvement was diagnosed in the presence of subepicardial late gadolinium enhancement (LGE) in at least 3 contiguous segments in the same short-axis slice at cardiac magnetic resonance, independent of whether it fulfilled the 2010 Task Force criteria for right-dominant ACM (biventricular ACM) or not (left-dominant ACM); in this latter case, diagnosis was reached after careful exclusion of other differential diagnosis, and only when at least one of the following features was present: likely pathogenic/pathogenic genetic variant associated with ACM; familial history of ACM; electrocardiographic abnormalities suggestive of ACM with LV involvement. Advanced HF was defined as NYHA functional class III/IV and/or referral for heart transplantation. Median follow-up was 6 years. Results: Forty-four out of 174 ACM patients (25%) developed advanced HF: 10 right-dominant ACM and 34 with LV involvement. Twenty ACM patients were initially diagnosed with dilated cardiomyopathy; as such, development of advanced HF in 17 cases preceded the diagnosis of ACM. Five patients were diagnosed with ACM after heart transplantation, by histological examination. In the other 22, median time from ACM diagnosis to advanced HF development was 4 years. As compared to those without, advanced HF patients were more likely to present LV involvement. During clinical course, 20 (46%) advanced HF patients received at least one appropriate ICD intervention, with 13 experiencing an electrical storm. Twenty-six (59%) patients required HF-related hospitalization, and 32 (72%) were referred for heart transplantation with 25 ultimately receiving it. ACM patients with advanced HF, compared to those without, experienced a higher rate of mortality (36% vs. 6%; OR 3.5 [95%CI: 1.4-8.7], p=0.01) and ventricular arrhythmic events (41% vs. 11%; OR 2.4 [95%CI: 1.1-5.0], p=0.02). Conclusions: Advanced HF progression in ACM is not rare, and occurs more frequently in variants with LV involvement. Advanced HF is associated with increased mortality and arrhythmic risk.